The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00421-018-3906-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function and mechanics following prolonged endurance exercise: an update and meta-analysis with insights from novel techniques

Abstract: BackgroundThe cardiac consequences of undertaking endurance exercise are the topic of recent debate. The purpose of this review is to provide an update on a growing body of literature, focusing on left ventricular (LV) function following prolonged endurance exercise over 2 h in duration which have employed novel techniques, including myocardial speckle tracking, to provide a more comprehensive global and regional assessment of LV mechanics.MethodsProspective studies were filtered independently following a pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
5
22
1
Order By: Relevance
“…In a meta-analysis by Middleton et al (2006) it was demonstrated that only ultradistance events >10 h elicited reductions in LVEF in trained individuals. In contrast, LV E/A ratio is reduced following endurance exercise as short as 45 min (Donaldson et al, 2019), and E' is reduced after 2 h of exercise (Lord et al, 2018). Left ventricular diastolic function, when assessed via classic measures of E/A ratio and tissue Doppler imaging, was reduced following all exercise durations in the present investigation, as is consistent with previous literature (Middleton et al, 2006;Lord et al, 2018;Donaldson et al, 2019), suggesting that transmitral flow velocities are altered with most forms of aerobic exercise.…”
Section: Left Ventricular Alterationssupporting
confidence: 90%
See 3 more Smart Citations
“…In a meta-analysis by Middleton et al (2006) it was demonstrated that only ultradistance events >10 h elicited reductions in LVEF in trained individuals. In contrast, LV E/A ratio is reduced following endurance exercise as short as 45 min (Donaldson et al, 2019), and E' is reduced after 2 h of exercise (Lord et al, 2018). Left ventricular diastolic function, when assessed via classic measures of E/A ratio and tissue Doppler imaging, was reduced following all exercise durations in the present investigation, as is consistent with previous literature (Middleton et al, 2006;Lord et al, 2018;Donaldson et al, 2019), suggesting that transmitral flow velocities are altered with most forms of aerobic exercise.…”
Section: Left Ventricular Alterationssupporting
confidence: 90%
“…While recreational athletes report participation in events like ultramarathon to improve physical health (Hoffman, 2016), the physiological consequences of participation are incompletely characterized. From a cardiac perspective, there is evidence that prolonged strenuous exercise may transiently alter both left ventricular (LV) (Middleton et al, 2006;Lord et al, 2018) and right ventricular (RV) (Oxborough et al, 2011;Elliott and La Gerche, 2014) function. This alteration is often termed "exercise induced cardiac fatigue, " and event duration and participant cardiorespiratory fitness are thought to play a role in the severity of the associated change (Middleton et al, 2006;La Gerche et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bouts of intensive or long-lasting exercise (such as marathons or ultra-marathons) have been shown to increase blood levels of cardiac troponin, a known selective marker for myocardial injury and a major component of a current diagnosis of myocardial infarction [4][5][6][7]. Troponin rise after exercise is 2 of 9 usually discrete with levels returning to reference values within hours [8] and may be accompanied by an increase of natriuretic peptide levels and transient decrease of left or right ventricular systolic function without long-term consequences [9][10][11][12]. In line with that, recent studies with new imaging techniques demonstrated that intensive endurance training does not seem to promote myocardial fibrosis [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%